Subsistence variations and landscape use among maritime hunter-gatherers. A zooarchaeological analysis from the Beagle Channel (Tierra del Fuego, Argentina) - Tivoli, Angelica Montserrat (2011)
Changes in the exploitation of resources among prehistoric hunter-gatherer-fishers of the Beagle Channel (Southern South America) are examined in this paper. Archaeological investigations show the prevalence of maritime hunter-gatherer organization throughout the occupation of the region (ca. 6400 BP e 19th century). Notwithstanding, variations in the exploitation of different kind of animal resources have been detected, and a concomitant reorientation in the landscape use is then inferred. Zooarchaeological evidence from five shellmiddens is analyzed here: evenness measures and relative abundance prey types are used to evaluate such adjustments. Results indicate the major utilization of coastal and terrestrial ecozones and the predominance in the exploitation of mammals (pinnipeds and guanacos) in ancient occupations. While, during the Late Holocene an expansion in ranges of maritime mobility for subsistence is detected, whichwas associated with an increase in the representation of birds and fish in the zooarchaeological record.